Psychiatrists in combat mental health clinicians' experiences in the war zone - Ritchie, Elspeth Cameron; Warner, Christopher H.; McLay, Robert N. (Springer, 2017)
This book tells the professional and personal experiences of American military psychiatrists and their fellow mental health providers in the longest conflict in American history. The volume consists of 20 short first-person case studies from mental health providers who have been risking their lives while treating patients in the battlefield since 9/11.